2020
DOI: 10.3164/jcbn.20-37
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of including probiotics to <i>Helicobacter pylori</i> eradication therapies

Abstract: The eradication rate of Helicobacter pylori ( H. pylori ) with proton pump inhibitors, amoxicillin, and clarithromycin has reportedly decreased. Some studies have found probiotics to be useful in eradicating H. pylori , but these effects have not been sufficiently investigated. We aimed to elucidate the role of probiotics in eradicating H. pylori infection. Patients in our hospital with H. pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…In clinic, the importance of either H. pylori eradication or their regulation impose significant impact on either gastric cancer prevention or gastric diseases amelioration, for which several kinds of intervention like natural products, probiotics, and more effective anti-H. pylori therapy are under active investigation. (68)(69)(70)(71) In conclusion, walnut seems to be very effective and attractive because of well-acknowledgement as "pharmanutrient" against H. pylori infection. However, welldesigned clinical trial should be followed.…”
Section: Discussionmentioning
confidence: 95%
“…In clinic, the importance of either H. pylori eradication or their regulation impose significant impact on either gastric cancer prevention or gastric diseases amelioration, for which several kinds of intervention like natural products, probiotics, and more effective anti-H. pylori therapy are under active investigation. (68)(69)(70)(71) In conclusion, walnut seems to be very effective and attractive because of well-acknowledgement as "pharmanutrient" against H. pylori infection. However, welldesigned clinical trial should be followed.…”
Section: Discussionmentioning
confidence: 95%
“…When combined with a triple therapy of omeprazol, clarithromycin, and amoxicillin, pre-treatment of patients with L. acidophilus, S. faecalis , and B. subtilis for two-weeks improved the eradication rate by 18.7% compared to the control ( Du et al, 2012 ). A 24-month clinical trial involving nearly 500 subjects found similar results with a combination of probiotic treatment and triple therapy increasing eradication rate by 7% ( Rieko et al, 2020 ). It is proposed that this colonization reduction may be due to a decrease in the biotic load despite H. pylori antimicrobial resistance ( Du et al, 2012 ).…”
Section: Regulation Clinical Efficacy and Safetymentioning
confidence: 84%
“…The incidence of peptic ulcers caused by H. pylori infection has markedly decreased in Japan because eradication therapy for H. pylori has been widely accepted. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Additionally, the infection rate of H. pylori has markedly decreased in Japan, (20,(31)(32)(33) especially in younger generations; the infection rate in junior high school students is <5%. (34) PPIs have recently become more frequently prescribed for secondary prevention of peptic ulcers and upper GI bleeding induced by NSAIDs and/or aspirin in Japan, (2,(35)(36)(37)(38) although the prescription of aspirin has increased in a time-dependent manner as demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 99%